How does family economic background shape adolescents’ present- and future-oriented well-being? Roles of perceived discrimination and grit - Yinghang Huang; Xiaojing Wu; Muhaned Tamim; Xiayun Jin; Lin Ma; Jie Xu (BMC Psychology)
Abstract Background The association between family socioeconomic status (SES) and adolescent well-being is complex, involving both present and future dimensions. This study examines perceived discrimination as a mediator in this association and grit as a potential moderator buffering the adverse effects of low SES and discrimination on adolescent well-being. Methods The study surveyed 2,202 students (53.3% male; ages 11–15 years) from Northeast China. The participants completed questionnaires assessing subjective socioeconomic status, objective socioeconomic status (parental education and occupation), perceived discrimination, grit, and both present- and future-oriented well-being. Mediation analyses and moderated mediation models were employed to test the hypothesized relationships. Results Perceived discrimination mediated the association between both subjective and objective socioeconomic status (SES) and adolescent well-being, with comparable indirect effect magnitudes for both SES types. Grit moderated the association between perceived discrimination and well-being, and the direct association between objective socioeconomic status and well-being. Grit’s moderating effects were stronger for future-oriented well-being compared to present well-being, indicating its relevance for long-term outcomes. Conclusions Findings indicate that family SES relates to adolescent well-being via perceived discrimination, and grit can mitigate these adverse impacts. This points to the potential value of interventions addressing systemic inequalities and strengthening psychological resources like grit among socioeconomically disadvantaged youth.